2005
DOI: 10.1016/j.acn.2004.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Driving Scenes test of the Neuropsychological Assessment Battery (NAB) and on-road driving performance in aging and very mild dementia

Abstract: The Driving Scenes test of the new Neuropsychological Assessment Battery (NAB; [Stern, R.A., & White, T. (2003a). Neuropsychological Assessment Battery. Lutz, FL: Psychological Assessment Resources, Inc.]) measures several aspects of visual attention thought to be important for driving ability. The current study examined the relationship between scores on the Driving Scenes test and on-road driving performance on a standardized driving test. Healthy participants performed significantly better on the Driving Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
1
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 22 publications
1
56
1
2
Order By: Relevance
“…Some neuropsychological tests that have been moderately correlated with unsafe driving in previous studies (e.g., NAB and Mazes; Brown et al, 2005b;Whelihan et al, 2005) did not relate to driving status in this comparison study. Findings from this study suggest that these tests may relate most strongly to severity of cognitive impairment rather than being specifically predictive of driving status.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Some neuropsychological tests that have been moderately correlated with unsafe driving in previous studies (e.g., NAB and Mazes; Brown et al, 2005b;Whelihan et al, 2005) did not relate to driving status in this comparison study. Findings from this study suggest that these tests may relate most strongly to severity of cognitive impairment rather than being specifically predictive of driving status.…”
Section: Discussioncontrasting
confidence: 64%
“…The cognitive domains of memory, visuospatial skills, executive function, and psychomotor speed were specifically examined because previous studies have found a relationship between these cognitive abilities and driving performance (Brown et al, 2005b;Marcotte et al, 1999;Reger et al, 2004). All tests were administered and scored by a neuropsychologist according to standardized procedures outlined in test manuals.…”
Section: Procedures and Measuresmentioning
confidence: 99%
“…We propose a novel battery of driving-related sensory-motor and cognitive tests-SMCTests-which has shown good face validity, stability, reliability, and construct validity in normal subjects. SMCTests has also previously been used to model on-road driving ability in drivers with brain disorders, with a classification accuracy for pass or fail of 94% (Innes et al, 2007), which compares well with classification accuracies of 70%-94% in other test batteries (Brown et al, 2005;Fox, Bowden, Bashford, & Smith, ing on-road driving ability than would the standard neuropsychological cognitive tests (Figure 3). Specifically, subjects felt that the novel cognitive tests of DecisionMaking and Planning would be most predictive of on-road driving ability.…”
Section: Discussionmentioning
confidence: 82%
“…Standardized road tests are considered the gold standard for monitoring driving fitness in older adults (Carr & Ott, 2010). Standardized road test performance relates well to available office-based cognitive assessments and to history of motor vehicle crashes (Barrash et al, 2010;Brown, Stern, et al, 2005;Dawson, Anderson, Uc, Dastrup, & Rizzo, 2009;Fitten et al, 1995;Grace et al, 2005). The standardized road test is also a reasonable proxy for estimating older people's driving ability in their routine driving environments Ott et al, 2012).…”
mentioning
confidence: 99%